The Effectiveness of Cow Manure and Banana Peel Liquid Organic Fertilizer on the Growth of Rose Cuttings (Rosa Damascena) - Andre Darma Yogi Ginting; Najla Lubis; Maimunah Siregar (Sean Institute, 2026)
Rose plants (Rosa damascena) are ornamental plants that have high aesthetic and economic value and are widely cultivated through cutting techniques. The success of cutting growth is greatly influenced by the availability of nutrients. This study aims to determine the effectiveness of providing cow manure and liquid organic fertilizer (POC) from banana peels on the growth of rose cuttings. The study was conducted on the land of Panca Budi Development University, Sampe Cita Village, Deli Serdang Regency, North Sumatra province, from October 2025 to January 2026. The study used a 4x4 factorial Randomized Block Design (RBD) with 3 replications. The first factor was cow manure (T) consisting of T0 = 0 g/polybag, T1 = 1,000 g/polybag, T2 = 1,500 g/polybag, and T3 = 2,000 g/polybag. The second factor was banana peel POC (K) consisting of K0 = 0 ml/L water/plot, K1 = 150 ml/L water/plot, K2 = 300 ml/L water/plot, and K3 = 450 ml/L water/plot. The parameters observed included plant height, number of branches, number of shoots, number of leaves, leaf length, and stem diameter. The results showed that the application of cow manure had a significant to very significant effect on all observed parameters, while banana peel POC had a significant effect on several parameters. The interaction between the two treatments did not show a significant effect on all growth parameters. The best treatment was the application of cow manure at a dose of T3 = 2,000 g/polybag and banana peel POC K3 = 450 ml/L water/plot.